1994
DOI: 10.1192/bjp.165.4.493
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorder in Later Life: A Community Study

Abstract: It is important to evaluate personality in patients of all ages. While some older patients no longer meet criteria for personality disorder, maladaptive traits may become evident during times of stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
1
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 29 publications
2
20
1
1
Order By: Relevance
“…Much of the effect for age appeared in lower scores by older women on the Cluster B disorders, consistent with findings from both normal samples (Cohen et al, 1994) and incarcerated men (Harpur & Hare, 1994). In an exploratory study of the effect of age on lower order traits hypothesized to relate to PDs, the older women in this sample also differed from the younger women.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Much of the effect for age appeared in lower scores by older women on the Cluster B disorders, consistent with findings from both normal samples (Cohen et al, 1994) and incarcerated men (Harpur & Hare, 1994). In an exploratory study of the effect of age on lower order traits hypothesized to relate to PDs, the older women in this sample also differed from the younger women.…”
Section: Discussionsupporting
confidence: 76%
“…In a community sample of older adults, citizens over age 55 were less likely to have PDs overall, with the different levels almost wholly accounted for by the Cluster B disorders (Cohen et al, 1994). Fogel and Westlake (1990) also found that patients over age 65 had lower rates of PDs, and Reich, Nduaguba, and Yates (1988) found decreases in Cluster B disorders until age 60.…”
mentioning
confidence: 93%
“…The difference in the rate of personality disorders between our study (23.3%; 95% CI=13.4%-36.0%) and the majority of these population studies was substantial. This high rate in our elderly patients is even more striking considering that the prevalence of personality disorders declines with age (30,32). Our figure falls below the rates for personality disorders after traumatic brain injury reported by Van Reekum et al (8) (38%) and Hibbard et al (11) (66%).…”
Section: Discussionmentioning
confidence: 93%
“…However, our summed rate of SCID-II personality disorders and organic personality syndrome (30.0%) is close to the former figure. In our study, the most common personality disorders were avoidant (15.0%, 95% CI=7.1%-26.6%), paranoid (8.3%, 95% CI=2.8%-18.4%), and schizoid (6.7%, 95% CI=1.9%-16.2%) personality disorder, while in the population studies, the upper limits of the ranges of prevalences for these disorders have been 1.6%, 7.3%, and 1.6%, respectively (29)(30)(31). Also, Hibbard et al (11) reported that avoidant (26%) and paranoid (26%) personality disorders are common after traumatic brain injury.…”
Section: Discussionmentioning
confidence: 98%
“…Cross-sectional and longitudinal studies of PD, however, have usually failed to find support for the level of stability implied by the DSM definitions. Cross-sectional studies have generally concluded that many PDs are less prevalent among older adults than younger and/or middle-aged adults (Cohen et al, 1994; Coid, Yang, Tyrer, Roberts, & Ullrich, 2006; Gutiérrez et al, 2012; Samuels et al, 2002; Segal, Hook, & Coolidge, 2001); and longitudinal evidence suggests that, on average, most PDs show mean-level decreases over time in both clinical (Ferro, Klein, Schwartz, Kasch, & Leader, 1998; Grilo et al, 2004) and nonclinical samples (Crawford et al, 2005; Johnson et al, 2000; Lenzenweger, Johnson, & Willett, 2004). In short, self-reported data suggest that many PDs do “become less evident or remit with age,” as stated in the DSM-IV-TR (American Psychiatric Association, 2000, p. 688).…”
mentioning
confidence: 99%